2014
DOI: 10.1308/003588414x13824511649616
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of knife injuries at a London major trauma centre

Abstract: INTRODUCTIONNo national recording systems for knife injuries exist in the UK. Understanding the true size and nature of the problem of knife injuries is the first stage in reducing the burden of this injury. The aim of this study was to survey every knife injury seen in a single inner city emergency department (ED) over a one-year period.METHODSA cross-sectional observational study was performed of all patients attending with a knife injury to the ED of a London major trauma centre in 2011. Demographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 15 publications
4
38
0
1
Order By: Relevance
“…The cases were self‐reported as accidents (49%), assaults (43%) and deliberate self‐harm (8%). The majority of abdominal trauma caused superficial injuries only, while only 1.6% of all knife injuries involved a solid organ .…”
Section: Discussionmentioning
confidence: 99%
“…The cases were self‐reported as accidents (49%), assaults (43%) and deliberate self‐harm (8%). The majority of abdominal trauma caused superficial injuries only, while only 1.6% of all knife injuries involved a solid organ .…”
Section: Discussionmentioning
confidence: 99%
“…Young people are the most frequent victims of knife violence. 7 Male teenagers from deprived communities in urban areas are at particularly high risk, with a peak in incidence between the ages of 16 and 24 years. 1 2 8 Stab injuries in children are less common than in adolescents, but also predominantly affect those living in areas with the highest level of socioeconomic deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Bostrom et al 15% of deaths resulting from stab wounds were caused by stabs to the extremities ( 20 ). Furthermore, a recent study reported that among stab victims 19% suffered from multiple injuries ( 21 ). In such settings the control of hemorrhage can be difficult and time consuming.…”
Section: Discussionmentioning
confidence: 99%